Is VHB-JOURQUAL2 a Good Measure of Scientific Quality? Assessing the Validity of the Major Business Journal Ranking in German-Speaking Countries - Martin Eisend (BuR - Business Research, 2011)
This study examines the question of whether the journal ranking VHB-JOURQUAL 2 can be considered as a good measure for the construct scientific quality. Various rankings in business research provide the database for the analysis. The correlations between theses rankings are used to assess the validity of VHB-JOURQUAL 2 along various validity criteria. The correlations with rankings that measure the same construct based on different methods show that VHB-JOURQUAL 2 has acceptable, but moderate convergent validity. The validity varies considerably across disciplines, showing that the heterogeneity of business administration is not sufficiently represented by this overall ranking. The variability is related to the variation in members per discipline represented by the German Association for Business Research. Furthermore, the measure shows a weak correlation with acceptance rates as an indicator of nomological validity in some disciplines.
urn:nbn:de:0009-20-32103
Keywords: 650; VHB-JOURQUAL 2; journal standing; journal ranking; business research journals; evaluation of scholars; journal ranking methods; validity; Operations Research; Bibliometrie; Ranking-Verfahren; Wissenschaftsforschung; Deutschsprachiger Raum